2018
DOI: 10.1038/s41467-017-02795-4
|View full text |Cite
|
Sign up to set email alerts
|

AMPK activation counteracts cardiac hypertrophy by reducing O-GlcNAcylation

Abstract: AMP-activated protein kinase (AMPK) has been shown to inhibit cardiac hypertrophy. Here, we show that submaximal AMPK activation blocks cardiomyocyte hypertrophy without affecting downstream targets previously suggested to be involved, such as p70 ribosomal S6 protein kinase, calcineurin/nuclear factor of activated T cells (NFAT) and extracellular signal-regulated kinases. Instead, cardiomyocyte hypertrophy is accompanied by increased protein O-GlcNAcylation, which is reversed by AMPK activation. Decreasing O-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
148
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(162 citation statements)
references
References 68 publications
(112 reference statements)
11
148
2
Order By: Relevance
“…Instead, we observed an increase in alternative downstream uses of glucose; in addition to energy production, both our global gene expression and metabolomics analyses suggest that the excess imported glucose may be partially directed toward hexosamine and ECM biosynthesis, protein O‐/N‐GlcNAcylation, and the pentose phosphate shunt (Figure 8). Given that other studies have also observed changes in hexosamine biosynthesis and protein O‐GlcNAcylation in response to alterations in cardiac metabolism36 and hypertrophy,37 further study of these changes is warranted. In addition to the observed diversion of glucose toward alternative downstream fates, glucose metabolism correlated negatively with heart size.…”
Section: Discussionmentioning
confidence: 98%
“…Instead, we observed an increase in alternative downstream uses of glucose; in addition to energy production, both our global gene expression and metabolomics analyses suggest that the excess imported glucose may be partially directed toward hexosamine and ECM biosynthesis, protein O‐/N‐GlcNAcylation, and the pentose phosphate shunt (Figure 8). Given that other studies have also observed changes in hexosamine biosynthesis and protein O‐GlcNAcylation in response to alterations in cardiac metabolism36 and hypertrophy,37 further study of these changes is warranted. In addition to the observed diversion of glucose toward alternative downstream fates, glucose metabolism correlated negatively with heart size.…”
Section: Discussionmentioning
confidence: 98%
“…Under conditions of chronic stress, however, this prolonged response may lead to adverse consequences. Recently, AMPK was shown to phosphorylate Gfat1 and suppress its enzymatic activity under pressure overload 25 . Indeed, glucose infusion in the heart leads to stimulation of the HBP, which is associated with pathological remodeling 27 .…”
Section: Controlmentioning
confidence: 99%
“…Moreover, O-GlcNAc protein modification in hearts is increased in various models of cardiac hypertrophic growth 24 . More recently, Gelinas et al 25 showed that 5′-adenosine monophosphate-activated protein kinase (AMPK) prevents pathological cardiac hypertrophy by promoting Gfat1 phosphorylation and thereby decreasing O-GlcNAc modification in the heart. Despite these findings, it remains to be answered whether the upregulation of HBP by pressure overload plays a causal role in pathological cardiac remodeling.…”
mentioning
confidence: 99%
“…For instance, both resveratrol and metformin share analogous beneficial effects in counteracting oxidative stress in endothelial cells by activating AMPK (Cheang et al, ). They both can attenuate cardiac hypertrophy by activating AMPK (Gélinas et al, ). In a previous study, resveratrol and metformin may synergistically lower hepatic lipid contents and systolic blood pressure in Type 2 diabetes patients (Timmers et al, ).…”
Section: Molecular Basis Of Resveratrol Actionmentioning
confidence: 99%